Aerodynamic shape design of transonic airfoils using stochastic optimisation methods and computational fluid dynamics - Lee, Shiang Long. (2008)
The present study investigates a number of airfoil design optimisation problems. A CFD method based on a finite volume method is used to solve the compressible Navier-Stokes equations. It is used to capture the details of flow separation, boundry-layer and turbulent flow characteristics that provide a good estimate of the design objective functions. The objective functions are then optimised in the design process by using stochastic optimisation methods of Simulated Annealing, a number of variants of Simulated Annealing and Genetic Algorithm. The study addresses both constrained and unconstrained airfoil design problems by integrating CFD, stochastic optimisation methods and Computer-Aided Geometry. The airfoil shapes are represented by using parametric functions to achieve an efficient optimisation process that obtains optimum airfoil shapes satisfying the desired design objectives and constraints. An attempt is made to improve the efficiency of the Simulated Annealing scheme by introducing a new variant, i.e. Simulated Annealing with Constant Acceptance Ratio (SACAR).